Economic Literacy and Money Illusion : An Experimental Perspective - Chytilová, Helena (2018)
The concept of money illusion, a recently resurrected phenomenon of behavioral economics,is a real fact of economic life, the potential role of which should no longer be dismissed.Despite money illusion being utterly suppressed by mainstream economists, small deviationsfrom rationality, together with trends in behavioral economics, alleviate the denial of moneyillusion induced by the rational expectations revolution. This book argues that money illusionseems to be a ubiquitous phenomenon, affecting various areas such as financial markets,housing markets, labor markets, consumption-saving decisions, and even development at theaggregate level induced by coordination issues. Furthermore, in light of the educationalefforts of central banks and other institutions, it is worth considering whether solid economictraining would provide guidance for the public regarding their decision-making and therebyalleviate the effects of money illusion. The emerging field of experimental economicsprovides a unique opportunity for us to verify the presence of money illusion. Specifically,attention is devoted to the experimental investigation of reduction in the direct and indirecteffects of money illusion with respect to the level of economic literacy acquired througheconomic education.